Running for health: Self-rated physical health, mental health, and well-being among fun runners in South Sulawesi - Aprilo, Ians; Arfanda, Poppy Elisano; Juhanis; Gani, Ruslan Abdul; Setiawan, Edi (UIR Press, 2025)
Background: This research explores how fun run participants in South Sulawesi perceive their physical health, mental health, and overall well-being, highlighting the holistic benefits of active lifestyles in promoting quality of life. Research Objectives: This study is the effect of fun runs on physical and mental health and well-being. Physical health is divided into 4 parts. Mental health consists of 4 parts. Mental well-being with 5 questions. Methods: This study used quantitative descriptive research. The subjects involved 76 from 11 communities in South Sulawesi. The instrument used the Quality-of-Life SRH (SF-36), which contains that must be assessed by the subjects. The data collection was done through Google Forms and shared through each or between communities. The answers were assessed independently based on what is thought and are subjective; these answers are early predictors of everyone’s health. This questionnaire was distributed from January 25 to April 20, 2024. Findings and Results: The results of the significance calculation are fun. A run against physical health obtained a t-value of 3.494 and p of 0.001, mental health obtained a t-value of 3.671 and p of 0.000, and mental well-being obtained a t-value of 3.613 and p of 0.000. Conclusion: Fun runs have an impact on physical and mental health and mental well-being. This study cannot be generalised to other research subjects due to the limitations of the researchers. However, the results of the study were developed and socialised so that the people of South Sulawesi are more active in living and achieving long-term life goals.